Traditional Healers as Health Care Providers for the Latine Community in the United States, a Systematic Review (Mary Ann Liebert, 2022)
Background: Due to structural barriers to accessing the biomedical health care system, traditional healers (THs) often serve as the first point of contact for health care by Latine individuals in the United States. A recent assessment of the extent of use of THs by the Latine community is lacking. Methods: We conducted a systematic review of the literature published between 2000 and 2020, to assess the prevalence of use of THs by U.S. Latine individuals, health conditions for which care was sought, reasons for their use, and extent of TH use and dual use that is of biomedical health care and TH together. Primary inclusion criteria for studies included: (1) published in English, (2) focus on THs, (3) pertained to Latine individuals residing in the United States, and (4) published since 2000. Results: Eighty-five studies were reviewed; 33 met inclusion criteria. Under the overarching term of curanderos, 4 subtypes of THs were identified: sobadores, yerberos, espiritualistas, and hueseros. The lifetime prevalence of TH use varied from 6% to 67.7% depending on the demographic differences among the Latine individuals in these studies. Primary reasons for seeking care from THs were accessibility/convenience, affordability, and linguistic and cultural congruence. Discussion: The use of THs is highly prevalent for Latine community residing in the United States because they are accessible, affordable, and provide culturally and linguistically compatible care, indicating that they offer an alternative that addresses systemic structural barriers to biomedical health care. Further research on the efficacy and safety of the treatments rendered by THs and how their care might be optimally coordinated with biomedical health care, could improve health equity and access to care among Latine individuals in the United States.